Assessment of river water quality and treats to safe water supply in Malaysia / Adam Harith Zafrul Fazry - Adam Harith, Zafrul Fazry (2022)
The spatial water quality trends of sixteen monitoring stations distributed along the Langat River basin are investigated in this study, which spans the years 2016 to 2020. The health and status of the stream were examined and appraised from numerous angles. First, agglomerative HCA was used, in which sixteen monitoring sites were grouped into four groups based on similar land use practices and contaminants. Then, using PCA, it was determined which contaminants were the most significant contributors to water contamination. BOD, COD, and NH3 were determined to be the main proponents based on PCA. The findings were further validated by the M-K test, which revealed a growing trend in COD and BOD. The findings of this study may enable decision-makers in developing a more comprehensive policy, including, without a doubt, upgrading treatment facilities into an upgraded water treatment plant that will aid in accomplishing smooth water supply operations. We can infer from this evaluation that statistical analysis can find substantial data on the geographical fluctuation of a vast and complex river water quality dataset.